2007
DOI: 10.1152/ajpendo.00589.2005
|View full text |Cite
|
Sign up to set email alerts
|

A mathematical model of the mitochondrial NADH shuttles and anaplerosis in the pancreatic β-cell

Abstract: The signal propagation goes via mitochondrial metabolism, which relays the signal to different routes. One route is an increased ATP production that, via ATP-sensitive K ϩ (KATP) channels, modulates the cell membrane potential to allow calcium influx, which triggers insulin secretion. There is also at least one other "amplifying" route whose nature is debated; possible candidates are cytosolic NADPH production or malonyl-CoA production. We have used mathematical modeling to analyze this relay system. The model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 108 publications
1
27
0
Order By: Relevance
“…Overall, these experimental studies support the hypothesis that activation NADH/NAD ϩ shuttling occurs in exercising skeletal muscle. This conclusion is also supported by other in silico studies (99). 6, C-F) and cytosolic redox state (Fig.…”
Section: Activation Of Transport Activity For Reducing Equivalentssupporting
confidence: 88%
“…Overall, these experimental studies support the hypothesis that activation NADH/NAD ϩ shuttling occurs in exercising skeletal muscle. This conclusion is also supported by other in silico studies (99). 6, C-F) and cytosolic redox state (Fig.…”
Section: Activation Of Transport Activity For Reducing Equivalentssupporting
confidence: 88%
“…This model could reproduce oscillations in glycolytic metabolites and predict a dose-response curve for ATP for increasing concentrations of D-glucose. Other pancreatic β-cell-specific models have been developed for specific parts of the pathway, such as NADH shuttles [35] and the initial section of glycolysis [35],[36]. This glycolytic model underlines the dependency of the occurrence of oscillations as a function of glucokinase, aldolase, phosphofructokinase and GAPD activities.…”
Section: Introductionmentioning
confidence: 99%
“…This is accomplished in ␤-cells partly via mitochondrial malate/aspartate and glycerolphosphate shuttles (12), and via PMET, as we suggest here and by an earlier study which demonstrated that NADH could be reoxidized despite blockage of mitochondrial shuttles in pancreatic ␤-cells. The "presence of an unknown cytosolic factor re-oxidizing cytosolic NADH," was suggested (12,45) based on the observation that, despite blockage of mitochondrial shuttles, glycolytic flux remained unchanged (12).…”
mentioning
confidence: 99%